2018
DOI: 10.7717/peerj.5812
|View full text |Cite
|
Sign up to set email alerts
|

Home sick: impacts of migratory beekeeping on honey bee (Apis mellifera) pests, pathogens, and colony size

Abstract: Honey bees are important pollinators of agricultural crops and the dramatic losses of honey bee colonies have risen to a level of international concern. Potential contributors to such losses include pesticide exposure, lack of floral resources and parasites and pathogens. The damaging effects of all of these may be exacerbated by apicultural practices. To meet the pollination demand of US crops, bees are transported to areas of high pollination demand throughout the year. Compared to stationary colonies, risk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 76 publications
0
37
0
1
Order By: Relevance
“…However, large pollination events bring bees and colonies from all over the country and with unknown pathogen loads into close contact: a perfect storm for epidemic disease transmission. One study showed that BQCV and SBV are significantly more prevalent in migratory bees [110], and this was confirmed for colonies being transported for almond pollination [111]. However, in the latter study, BQCV levels were similar between the migratory and the stationary colonies one month after they returned to their home apiaries.…”
Section: Global Dissemination Of Viruses Of the Honey Beementioning
confidence: 77%
“…However, large pollination events bring bees and colonies from all over the country and with unknown pathogen loads into close contact: a perfect storm for epidemic disease transmission. One study showed that BQCV and SBV are significantly more prevalent in migratory bees [110], and this was confirmed for colonies being transported for almond pollination [111]. However, in the latter study, BQCV levels were similar between the migratory and the stationary colonies one month after they returned to their home apiaries.…”
Section: Global Dissemination Of Viruses Of the Honey Beementioning
confidence: 77%
“…Specifically, the rate of change in DWV abundance decreased from 0-100 days of the study and then increased from 150-250 days of the study (Fig 8). The time period between 0 and 100 days (i.e., November 2015 and March 2016) of the study encompasses the transport of colonies from Montana to California for almond pollination, which is noteworthy since reports on pathogen abundance before and after transportation events have indicated that pathogen load may increase [92,104]. In addition, prior to this transportation event, all colonies in this study were treated with miticides to reduce Varroa destructor mite infestation levels.…”
Section: Plos Onementioning
confidence: 99%
“…The Canadian National Honey Bee Health Survey data includes virus analysis of over 2,500 apiary-level samples (i.e., samples from 10 colonies per apiary) collected between July–September 2017, and indicates a high incidence of BQCV, DWV, LSV2, and SBV [ 90 ]. There have been relatively few longitudinal monitoring studies performed at the colony or superorganism level [ 53 , 89 , 91 , 92 ]. Previous studies indicate that virus prevalence and abundance varies with sample date (or season) and that peak abundance typically coincides with increased brood rearing and foraging activities during the summer months in temperate climates [ 53 , 54 , 85 ] (reviewed in [ 44 , 55 ]).…”
Section: Introductionmentioning
confidence: 99%
“…Without adequate forage, beekeepers must supply colonies with sucrose syrup and artificial pollen (Alger et al, 2018). To reduce the amount of food supplements that must be purchased, many commercial beekeeping operations move colonies from one blooming crop to another (Bond, Plattner, and Hunt, 2014).…”
Section: Regional Variation In the Us Beekeeping Industrymentioning
confidence: 99%